Neptun, an interdisciplinary scientific project to improve performance in swimming and para-swimming - Seifert, Ludovic; Carmigniani, Rémi; Pla, Robin; Domingo, Guillaume (Réflexions Sport, 2024)
The objective of NePTUNE project, “Swimming and Para-swimming: All United with our Elites”, is to provide the French coaches and swimmers with tools and methods (1) to evaluate the key performance factors (stroke rate/stroke length ratio, velocity, water resistance, force, gliding efficiency, motor coordination, etc), (2) to identify the different performance profiles in order to individualize training, (3) to perform physical models in order to optimize performance. To achieve this main objective, we started by analysing competitions, in particular to improve the race management strategies of French swimmers and gain a better understanding of opposing strategies. We then assessed the key factors mentioned above in experimental situations, from which knowledge can be transferred to coaches for monitoring swimmers. To reach these objectives, we built an interdisciplinary project with three axes of research mixing computational science and computer vision, biomechanics, motor control, physiology, physics, fluid mechanics and applied mathematics: (1) Tracking and pacing strategies, (2) Coordination, propulsion and energetics, (3) Water resistance and drafting.